Towards a Cognitive Distortion Conditional - VIKTORIIA DENISOVA (Manuscrito, 2025)
Abstract Cognitive distortions, systematic biases in thinking that lead to erroneous beliefs and emotional distress, are challenging to identify and address due to their extensive variability and context-dependent nature. This paper explores the limitations of traditional approaches, such as Beck’s cognitive model of depression, in consistently detecting these distortions across diverse therapeutic settings. This approach uses conditional statements to help reframe distorted thoughts. It is based on relevance theory, which emphasizes how context and cognitive effects play a crucial role in effective communication. By focusing on the pragmatic relationships within conditional statements, therapists may better understand and address distorted thinking patterns. This approach aligns with non-labeling strategies in Cognitive Behavioral Therapy (CBT) and Rational Emotive Behavior Therapy (REBT), fostering a more collaborative therapeutic process. The synthesis of conditional statements with relevance theory offers a structured framework for addressing cognitive distortions, potentially improving therapeutic interventions.